The Impact of Re-Operation, Relatives and Race on the Oculocardiac Reflex During Strabismus Surgery - Arnold RW (Dove Medical Press, 2020)
Robert W Arnold,1 Ainsley R Rinner,2 Andrew W Arnold,3 Brion J Beerle4 1The Alaska Blind Child Discovery, Alaska Children’s EYE & Strabismus, Anchorage, AK, USA; 2Grace Christian School, Anchorage, AK, USA; 3Pacific Northwest University College of Osteopathic Medicine, Yakima, WA, USA; 4Chugach Anesthesia Group, Anchorage, AK, USACorrespondence: Robert W ArnoldAlaska Children’s EYE & Strabismus, 3500 Latouche #280, Anchorage, AK 99508, USATel +1 907 561-1917Fax +1 907 563-5373Email eyedoc@alaska.netPurpose: The oculocardiac reflex (OCR) is a trigeminovagal bradycardia elicited by tension on an extraocular muscle (EOM). Using three decades of observational data, we investigated whether or not individual strabismus patients are prone to oculocardiac reflex.Patients and Methods: All patients undergoing strabismus surgery from 1992 to 2019 had deliberate 10-second, 200-gram square-wave tension on extraocular rectus muscles with anesthetic variables recorded. OCR was defined as the maximally tension-altered heart rate as a percent of stable baseline heart rate.Results: OCR was compared in 2532 original cases with 323 re-operations. The 169 cases that used anticholinergics (99% OCR) were excluded from the analysis. The median OCR, a 15% drop, was found to be 85% (95% CI 39%, 102%,; range 5– 151%). Factors that showed a significant effect on the OCR were the type of EOM with lateral rectus least (Kruskal–Wallis X2(3)=8, p< 0.05), and adults had less OCR compared to the children (X2(2)=105, p< 0.01). Factors that showed an augmenting effect on the OCR were peri-operative opioids (X2(6)=62, p< 0.01) and Caucasian race (X2(4)=12, p< 0.02). Gender and iris color were not found to have an impact on OCR. Re-operations and first-degree relatives did not differ from age-matched controls, but EOM- and opioid-adjusted re-operations correlated with their initial cases (r=0.37).Conclusion: We confirmed the previously published blocking effect of atropine, augmenting impact of opioids, and an inverse relationship of age on OCR. There was a weak proclivity for individuals to be prone to OCR. We found an impact of race with Caucasians having more OCR.Keywords: trigemino-vagal reflex, re-operation, race, opioid, strabismus surgery, bradycardia